First International Symposium on Urban Development: Koya as a Case Study 2013
DOI: 10.2495/isud130031
|View full text |Cite
|
Sign up to set email alerts
|

Production of skin lotions/creams from Hammam Jalli’s mud

Abstract: There are a number of natural springs throughout the Kurdistan region. They are located in different geographical areas and each of them may differ from another in odder and mineral contents. These springs are known by locals in Kurdistan under various names, for example, Hammam, Garaw, Ganaw or Ganau. Hammam Jalli is one of these springs which is located near the city of Koya and is attracting thousands of local people every year, mainly, those who are suffering from skin diseases such as psoriasis, urticaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The pH value measured parameter for almost all of the studies in Erbil province except study by Zangana et al (2014) and Jadoon et al (2015) .The outcomes of all tests showed that the highest pH Value is 8.9 in Zone two in Erbil city (Daham et al, 1998). The pH value of water in this area is out the range of standard for drinking water (6.5-8.5) (USEPA, 2018).…”
Section: Ph Valuementioning
confidence: 95%
See 1 more Smart Citation
“…The pH value measured parameter for almost all of the studies in Erbil province except study by Zangana et al (2014) and Jadoon et al (2015) .The outcomes of all tests showed that the highest pH Value is 8.9 in Zone two in Erbil city (Daham et al, 1998). The pH value of water in this area is out the range of standard for drinking water (6.5-8.5) (USEPA, 2018).…”
Section: Ph Valuementioning
confidence: 95%
“…Outside Erbil city, Groundwater Koya and Soran Districts are assessed by Babir and Ali (2016), Zangana et al (2014), andAl-Barwary et al (2018). Babir and Ali (2016) investigated Thirty wells and three springs at Koya Basin.…”
Section: Erbil Provincementioning
confidence: 99%